Analisis Pengaruh Mudharabah Financing, Musyarakah Financing, dan Ijarah Leases Terhadap Profitability Bank Syariah (PT. Bank Bca Syariah) Periode 2017-2021 - Ratna Komala; Isro’iyatul Mubarokah (Peneliti.net, 2022)
Research activities were conducted with the aim of knowing and testing the impact of Mudharabah Financing, Musyarakah Financing and Ijarah Lease on PT Bank BCA Syariah's profitability. The sampling method is a non-probability sample, the population covers all financial reports of Bank BCA Syariah, but the sample represents Bank BCA Syariah's quarterly financial statements from 2017 to 2021. The data used in this study are quantitative secondary data for the period 2017-2021. Tests were performed using the SPSS statistical program. Regarding Musyarakah Financing and Ijarah Lease, it is concluded that Musyarakah Financing and Ijarah Lease will not have a material impact on BCA Syariah's profitability. In contrast to the Mudharabah loan, the results showed that the Mudharabah loan had a significant impact on BCA Syariah Bank's profitability